Podziemny Informator Katowicki . pismo organizacji "Solidarność Walcząca" Katowice, Bielsko-Biała, Częstochowa, no. 32, 1988 - Orwell, George; Morawiecki, Kornel (Agencja Informacyjna Solidarności Walczącej Oddział Katowice, 1988)
Creation and circulation: Publication cooperated with Regionalna Komisja Koordynacyjna of the Śląsko-Dąbrowski region. In 1986-1987 suspended